2014
DOI: 10.1155/2014/306021
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional Computed Tomography Based Respiratory-Gated Radiotherapy with Respiratory Guidance System: Analysis of Respiratory Signals and Dosimetric Comparison

Abstract: Purpose. To investigate the effectiveness of respiratory guidance system in 4-dimensional computed tomography (4DCT) based respiratory-gated radiation therapy (RGRT) by comparing respiratory signals and dosimetric analysis of treatment plans. Methods. The respiratory amplitude and period of the free, the audio device-guided, and the complex system-guided breathing were evaluated in eleven patients with lung or liver cancers. The dosimetric parameters were assessed by comparing free breathing CT plan and 4DCT-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…As has been demonstrated in previous RGRT studies, 8,9,11,12 the PTV for all patients could be reduced, indicating a smaller total volume received the target dose. The PTV coverage and MTD were able to be maintained, suggesting that the target was just as effectively able to be treated.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As has been demonstrated in previous RGRT studies, 8,9,11,12 the PTV for all patients could be reduced, indicating a smaller total volume received the target dose. The PTV coverage and MTD were able to be maintained, suggesting that the target was just as effectively able to be treated.…”
Section: Discussionsupporting
confidence: 77%
“…Several recent studies using 4-dimensional computed tomography (4DCT) have shown that the use of patient-specific treatment margins and respiratory gating, rather than standard population-based treatment margins, can reduce normal tissue toxicity. [8][9][10][11][12] However, some have pointed out that the additional dosimetric benefits from respiratory gating may be modest and not justify the challenges of RGRT, including the increased time for treatment delivery and, consequently, the increased potential for uncertainty introduced from patient movement. 11,13 While increased treatment delivery time may not be of great concern for cases which only require a few minutes to complete, as may be true for some treatment plans using volumetric modulated arc therapy (VMAT), cases requiring longer treatment times, such as those using step-and-shoot intensity-modulated radiotherapy (IMRT), may benefit from the ability to estimate treatment time when assessing potential gating windows.…”
Section: Introductionmentioning
confidence: 99%
“…As has been demonstrated in previous respiratory gated radiation therapy studies [25,26,36,37], the planning target volume for all patients could be reduced, indicating a smaller total volume received the target dose. The PTV coverage and mean tumor dose were able to be maintained, suggesting that the target was just as effectively able to be treated.…”
Section: Discussionsupporting
confidence: 74%
“…A normal tissue complication probability (NTCP) model estimated that respiratory gating reduced pneumonitis risk from 43% to 32% for the highest-risk lung cancer patients [6]. Previous gating techniques have included free breathing gating with patient body surface measurements, or with fluoroscopic imaging of metal markers embedded near the tumor as a surrogate [1,[7][8][9][10]. Respiratory gating with audio guidance and visual feedback was also reported to improve the reproducibility and regularity of respiratory amplitude and period [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous gating techniques have included free breathing gating with patient body surface measurements, or with fluoroscopic imaging of metal markers embedded near the tumor as a surrogate [1,[7][8][9][10]. Respiratory gating with audio guidance and visual feedback was also reported to improve the reproducibility and regularity of respiratory amplitude and period [8]. To the authors' knowledge, no studies have reported respiratory gating under abdominal compression on a standard linear accelerator (linac).…”
Section: Introductionmentioning
confidence: 99%